Improved method for hydrochemical exploration of mineral resources - Luyen*, Nguyen Van; Savichev, Oleg G.; Domarenko, Viktor A.; Tin, Quach Duc (Vietnam Journal of Earth Sciences, 2017)
The article deals with a method for hydrochemical exploration and poorly studied areas based on the simulation and statistical modeling of the hydrochemical field. The peculiarity of the method is a prospecting area spotting under the following conditions: (1) the maximal ratio between river basin in the Riverhead without evident channel network and the total river basin; (2) the river network and tectonic deformations maximum; (3) presence of low-flow rate sections with relatively sharp breaks in grade of the water surface (outflow of rivers from mountainous areas onto the sub-mountain plain, extended sections of channel multi-branching). A sampling of 2-3 samples of surface water, 2-3 samples of river bed sediments, and 2-3 samples of ground water is taken at prospective sections and contiguous territories and the chemical composition determined. The geo-informational analysis and obtained data are used to determine the parameters of the model of the area under study, a predictive assessment of the hydrochemical indicators for prospective sections is carried out, and a detailed examination is planned and performed. The expected reduction in the cost of exploration compared to currently used methods is approximately 20%. References Alekseyenko V.A, 2005, Geochemical methods of ore deposits searches, Logos, Moscow. In Russian, 354p. Barsukov V.L, Grigoryan S.V, Ovchinnikov L. N, 1981. Geochemical methods of searches of ore deposits, Nauka, Moscow. In Russian, 318p. Benedini M., Tsakiris G, 2013. Water Quality Modelling for Rivers and Streams, Springer, Dordrecht, 287p. Chebotaryov N.P, 1962. Theory of stream runoff, Moscow State University, Moscow. In Russian, 464p. Dao Manh Tien, 1984. Methodology and features of geochemical specialization granitoide formations of Northern Vietnam, Azerbaijan State University, Baku. In Russian, 198p. Davis J. C, Statistics and data analysis in geology. 2nd edition, 1986, J. Wiley&Sons, Toronto, 266p. Dolgonosov B.V, Korchagin K.A, 2005. Probabilitical laws of the hydrochemical phenomena, Water resources, 4, 452-458. Domarenko V.A, 2012. Rational a technique of searches and a geology-economic estimation of ore deposits of rare and radioactive elements. Vol.1, Prediction. Exploration and Evaluation, Tomsk Polytechnic University Publishing, Tomsk. In Russian, 167p. Fadeyev V.V, Tarasov M.P, Pavelko V.L, 1989. A dependence of a total dissolved substancies and ionic composition of water of the rivers from their water regime, Hydromet, Leningrad. In Russian, 173p. Gamov M.I, Granovskaya N.V, Levchenko S.V, 2012. Metals in a coal. South Federal University, Rostov on Don, Russia, 45p. Garrels R.M, Christ C.L, 1965. Solution, minerals and equilibria, Freeman, Cooper, San Francisco. 450p. Grenthe I, Puigdomenech I, 1997. Symbols, standards and conventions, in: Modelling in aquatic chemistry. Nuclear energy agency, Paris, 35-68. Kolotov B.A, 1992. Hydrogeochemistry of ore deposits, Nedra, Moscow. In Russian, 192p. Kopylova Yu.G., Guseva N.V, 2014. Hydrogeochemical methods of searches of ore deposits, Tomsk Polytechnic University Publishing, Tomsk. In Russian, 179p. Kraynov S.R, Ryzhenko B.N, Shvets,V.M, 2004. Geochemistry of ground waters. Theoretical, Applied and Environmental Aspects, M: Science, Moscow. In Russian, 677p. Lasaga A.C, 1995. Fundamental approaches in describing mineral dissolution and precipitation rates, Reviews in Mineralogy. Chemical Weathering Rates of Silicate Minerals, Mineralogical Society of America, 31, 23-86. Lavyorov N.P. and Patyk-Kara N.G, 1997. Loosing ore deposits of Russia and countries of SNG, ed., Nauchny Mir, Moscow. In Russian, 453p. Lekhov A.V, 2010. Physical-geochemical hydrodynamic. KDU, Moscow. In Russian. 500p. Lerman A, 1979. Geochemical Processes Water and Sediment Environments, Wiley-Intersience Public, New York, 481p. Levashov S.P, Yakymchuk N.A., Korchagin I.N., Bozhezha D.N, 2010. Operative estimation of the ore-bearing prospects of the license areas and the areas of operating mines and ore deposits, Geoinformatika (Ukraina). In Ukr./Rus, 4, 23-30. Loucks D.P, Van Beek E, 2005. Water resources systems planning and management. An Introduction to Methods, Models and Applications, UNESCO Publishing, Turin, 680p. Martinson L. K, Malov Yu. I, 1996. Differential equations of mathematical physics. IGTU of N. E. Baumann Publishing, Moscow, XII (1996) 1-368. In Russian. Mezhevelovsky N. V. and Smyslov A.A., 2001. Mineral wealth of Russia. Vol.1, Mineral Resources, ed.. Mining Institute ICGC, Saint Peterburg - Moscow. In Russian, 285p. Mujumdar P.P, Kumar D.N, 2012. Floods in a Changing Climate. Hydrologic Modeling, Cambridge University Press, New York, USA, 177p. Nguyen Kinh Quoc, 2001. The Map of geological conditions and mineral resources in scale 1:200,000 of Bac Kan province, sheet F48-XV, Main Department of Geology and Minerals of Vietnam, Hanoi. In Vietnamese. Perelman A.I, 1979. Geochemistry, high school, Moscow. In Russian, 423p. Polikarpochkin V.V, 1976. Secondary auras and streams of dispersion, Science, Novosibirsk. In Russian, 407p. Requirements to manufacture and results multi-purpose geochemical mapping of scale 1:200.000, IMGRE, Moscow, 2002. In Russian. Rozhdestvensky A.V, Chebotaryov A.I, 1974. Statistical methods in a hydrology, Hydromet, Leningrad. In Russian, 424p. Savichev O. G, Domarenko V. A, 2014. Laws of change of the chemical composition of river sediments and their use in searches of minerals, Fundamental research, 6, 520-525. In Russian. Savichev O.G, 2010. Discharge regulation in surface water bodies, Water: chemistry and ecology, Vol. 9, 35-39. In Russian. Savichev O.G, 2015. Distribution of Inorganic Pollutants over the Depth of Upper Peat Deposit, Contemporary Problems of Ecology, 1, 118-124. Savichev O.G, Nguyen Van Luyen, 2015. Hydroecological condition between the Gam and Kau rivers (Northern Vietnam), Bulletin of Tomsk Polytechnic University, 7, 96-103. Savichev O.G, Nguyen Van Luyen, 2015. The technique of determining background and extreme values of hydrogeochemical parameters, Bulletin of Tomsk Polytechnic University, 9, 133-142. In Russian.